Genistein alleviates pressure overload‐induced cardiac dysfunction and interstitial fibrosis in mice. (13th January 2015) - Qin, Wei; Du, Ning; Zhang, Longyin; Wu, Xianxian; Hu, Yingying; Li, Xiaoguang; Shen, Nannan; Li, Yang; Yang, Baofeng; Xu, Chaoqian; Fang, Zhiwei; Lu, Yanjie; et al.
Abstract : Background and Purpose: Pressure overload‐induced cardiac interstitial fibrosis is viewed as a major cause of heart failure in patients with hypertension or aorta atherosclerosis. The purpose of this study was to investigate the effects and the underlying mechanisms of genistein, a natural phytoestrogen found in soy bean extract, on pressure overload‐induced cardiac fibrosis. Experimental Approach: Genisten was administered to mice with pressure overload induced by transverse aortic constriction. Eight weeks later, its effects on cardiac dysfunction, hypertrophy and fibrosis were determined. Its effects on proliferation, collagen production and myofibroblast transformation of cardiac fibroblasts (CFs) and the signalling pathways were also assessed in vitro . Key Results: Pressure overload‐induced cardiac dysfunction, hypertrophy and fibrosis were markedly attenuated by genistein. In cultured CFs, genistein inhibited TGFβ1‐induced proliferation, collagen production and myofibroblast transformation. Genistein suppressed TGFβ‐activated kinase 1 (TAK1) expression and produced anti‐fibrotic effects by blocking the TAK1/MKK4/JNK pathway. Further analysis indicated that it up‐regulated oestrogen‐dependent expression of metastasis‐associated gene 3 (MTA3), which was found to be a negative regulator of TAK1. Silencing MTA3 by siRNA, or inhibiting the activity of the MTA3‐NuRD complex with trichostatin A, abolished genistein's anti‐fibrotic effects. Conclusions and Implications: Genistein improved cardiac function and inhibited cardiac fibrosis in response to pressure overload. The underlying mechanism may involve regulation of the MTA3/TAK1/MKK4/JNK signalling pathway. Genistein may have potential as a novel agent for prevention and therapy of cardiac disorders associated with fibrosis. Linked Articles: This article is part of a themed section on Chinese Innovation in Cardiovascular Drug Discovery. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue-23